EFEKTIFITAS KOMUNIKASI INTERPERSONAL ORANG TUA TERHADAP REMAJA TENTANG PENDIDIKAN SEKS - R. Adisetiawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This study is accomplished to reveal the effectiveness of interpersonal communication that parents do to teenager in Jambi City about sex education. In implementation, the interpersonal communication can be very effective and not effective. The effectiveness is observed based on five general quality, that is: openness, empathy, supportiveness, positiveness, and equality. The type of research being held is descriptive quantitative with survey method. The result has confirmed that parents’ interpersonal communication to adolescence in Jambi City about sex education is effectiveKey Word: The interpersonal communication, parents, teenager, sex education